Employment Change after Takeovers: The Role of Executive Ownership. (1st March 2013) - Kuvandikov, Azimjon; Pendleton, Andrew; Higgins, David
Abstract The article examines the impact of executive ownership and other ownership and governance factors on employment change after takeovers. Drawing on a dataset of 235 takeovers, the results show that there is a reduction in employment in just over 50 per cent of the sample. Higher levels of executive share ownership are associated with lower probabilities of employee layoffs post‐takeover, and there is a positive relationship between executive ownership and employment growth. The effect of executive options on employment change is generally insignificant, as are the effects of other features of ownership and governance. The evidence suggests that executives with higher levels of ownership tend to mount takeovers of better‐performing firms and to implement takeovers aimed at growth.